Effect of Vermicompost in Media on Growth, Yield and Fruit Quality of Cherry Tomato (Lycopersicon esculentun Mill.) Under Net House Conditions. Issue 1 (2nd January 2018) - Truong, Ha Duy; Wang, Chong Ho; Kien, Tran Trung
ABSTRACT: Effects of VC application on tomato production and media properties can last for the third successive season, which was verified in this study to evaluate effects of VC application on growth, productivity and fruit quality of cherry tomato for the third season. Six treatments were designed similarly in the first and second seasons (unchanged design compared to the previous season), including: VC with rice husk ash (RHS) and coconut fiber (CF) 0% VC+ 50% RHS +50% CF (T1- control), respectively. 20%VC + 40% RHS + 40% CF(T2), 40% VC+ 30% RHS + 30% CF(T3), 60% VC + 20% RHS + 20% CF(T4), 80% VC + 10% RHS + 10% CF(T5), and 100% VC(T6). The results showed that the pH, EC, N, P, K, Ca, and Mg available in media were increased with the addition of VC. This finding revealed that the addition of VC significantly improved the physic-chemical media properties, increasing the EC and also increasing the macronutrients in the media resulting in substantial increased the yield and quality of tomato fruits. It is concluded that EC of VC was the key factor for the positive increase of the productivity and quality of tomato and the salinity (EC at 3.52 dS/m) causing restriction of water to fruits that resulted in the increase of the total soluble solids in tomato fruit and without affecting yield reduction.